A model of perfectionism, moral disengagement, altruism, and antisocial and prosocial behaviors in wheelchair athletes - Atkinson, F.; Martin, J. J.; Moore, E. W. G. (Adapted Physical Activity Quarterly, 2023)
Two forms of perfectionism were examined in the present study to see whether they predicted prosocial and antisocial behaviors in sport through moral disengagement and altruism in a sample of 327 wheelchair basketball and rugby athletes (M = 33.57 years, SD = 10.51; 83% male). Using structural equation modeling, the following significant direct and indirect effects were found. First, perfectionistic strivings positively predicted perceived prosocial behaviors and altruism. Second, perfectionistic concerns negatively predicted altruism and prosocial behaviors and positively predicted moral disengagement. Third, antisocial behaviors were positively predicted by moral disengagement and altruism. Furthermore, perfectionistic concerns indirectly predicted antisocial behaviors positively through moral disengagement and negatively through altruism. Finally, perfectionistic strivings positively predicted antisocial behaviors through altruism. Results provided partial support for the role of perfectionism in predicting prosocial and antisocial behaviors through moral disengagement among athletes with a disability.